RELOOKING BEAT GENERATION AND THE SPIRIT OF REBELLION IN HOWL - Mayanglambam, Buchi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the history of American Literature, the Beat Generation secures a position which defines the spirit of protest in literature. The Beat Generation or Beat Movement was not only a literary movement but also a cultural movement that spearheaded several counter-cultural movements in the second half of twentieth-century America. This essay explores and examines the rebellious traits of the Beat Generation by addressing their style, technique, language and content. While the Beats were against the conformist values of post-war America, they also challenged the established traditional values. These challenges and protests are studied by analysing Allen Ginsberg’s poem “Howl”. As “Howl” marked the beginning of a new era in literature. The poem is not only rebellious in style or content, but it paved the way to an end to censorship of literary texts. The paper briefly delves into the history of the movement and how it corresponds with the content of the “Howl”.